1996
DOI: 10.1152/ajpheart.1996.271.3.h1015
|View full text |Cite
|
Sign up to set email alerts
|

Brain angiotensin II tonically modulates sympathetic baroreflex in rabbit ventrolateral medulla

Abstract: The role of endogenous angiotensin II (ANG II) at the level of the rostral (RVLM) and caudal ventrolateral medulla (CVLM) in the control of sympathetic baroreflex function was investigated in urethan-anesthetized rabbits. The baroreflex relationship between mean arterial pressure and integrated renal sympathetic nerve activity (RSNA) was compared before and during microinfusion of saralasin, an ANG II receptor antagonist into RVLM or CVLM. The infusion of saralasin (20 pmol/min) into RVLM reduced the upper pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 0 publications
6
40
2
Order By: Relevance
“…Head and colleagues (21,33,34) showed in anesthetized and conscious rabbits that RVLM microinjection of ANG II increases, whereas microinjection of saralasin attenuates, the sensitivity of the baroreflex control of renal sympathetic activity. These data suggest an endogenous role for ANG II in the modulation of the sympathetic, but not the parasympathetic, component of the baroreceptor reflex at the RVLM (33)(34)(35).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Head and colleagues (21,33,34) showed in anesthetized and conscious rabbits that RVLM microinjection of ANG II increases, whereas microinjection of saralasin attenuates, the sensitivity of the baroreflex control of renal sympathetic activity. These data suggest an endogenous role for ANG II in the modulation of the sympathetic, but not the parasympathetic, component of the baroreceptor reflex at the RVLM (33)(34)(35).…”
Section: Discussionmentioning
confidence: 71%
“…The only data in the literature regarding the baroreflex control refer to the effect of ANG II or its antagonists on renal sympathetic nerve activity (RSNA). It has been shown that ANG II induces facilitation of the baroreflex at the RVLM (33-35) and inhibition of the baroreflex at the CVLM (35,40).It is becoming clear that ANG-(1-7) can act as a counterregulatory peptide of the RAS, because ANG-(1-7) has several effects that are opposite to those of ANG II (16,36). Centrally, lateral ventricular infusion (8,10,29) or microinjection into the NTS (12) of ANG-(1-7) facilitates the baroreflex control of HR, in contrast to the well-known inhibitory effect induced by ANG II (4, 32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microinjection of Ang II into the region of the A1 noradrenergic cells within the CVLM of the rabbit results in a depressor response (50). The most extensive study was performed by Saigusa and colleagues (51) who found that Ang II infusion into the CVLM of anesthetized rabbits decreased sympathetic activity and inhibited RSNA baroreflex while blockade of CVLM Ang receptors increased the sympathetic baroreflex but did not alter resting blood pressure or RSNA.…”
Section: Ang Actions Within the Caudal Ventrolateral Medullamentioning
confidence: 99%
“…ANG II receptors are also localized in the RVLM (1,2,4,5,25). Blockade of ANG II receptors in the RVLM decreases the baseline levels of SNA (44,45) and attenuates sympathetic responses evoked by stimulation of the hypothalamic paraventricular nucleus (PVN) (54), which suggests that endogenous ANG II or related peptides are involved in controlling the sympathetic outflow.…”
mentioning
confidence: 99%